1, 4-Bis(trimethylsilyl)-2, 5-dimethoxybenzene: a novel redox shuttle additive for overcharge protection in lithium-ion batteries that doubles as a mechanistic chemical probe1. Issue 14 (14th April 2015) - Huang, Jinhua; Shkrob, Ilya A.; Wang, Peiqi; Cheng, Lei; Pan, Baofei; He, Meinan; Liao, Chen; Zhang, Zhengcheng; Curtiss, Larry A.; Zhang, Lu
<x xml:space="preserve">Abstract</x> A novel redox shuttle additive, 1, 4-bis(trimethylsilyl)-2, 5-dimethoxybenzene, is shown to deliver superb overcharge protection of LiFePO4 electrode in Li-ion batteries.